Penyelesaian Gugatan Perkara Sederhana di Pengadilan Negeri Tebo - Syaftiani, Syaftiani (Universitas Jambi, Fakultas Hukum, 2023)
The Supreme Court of the Republic of Indonesia has issued a regulation on simple lawsuits in the form of Supreme Court Regulation (PERMA) Number 2 of 2015 concerning Procedures for Settling Simple Lawsuits which was later updated with PERMA Number 4 of 2019 concerning Amendments to PERMA Number 2 of 2015 concerning Procedures for Settling Simple Lawsuits. With these provisions, it is expected that the settlement of simple lawsuits is in accordance with the principles of Indonesian justice which is fast, simple and light in cost. This research was conducted to find out how to determine whether a lawsuit filed is a simple case or an ordinary case, and to see the effectiveness of the implementation of a simple lawsuit at the Tebo Class II District Court. This research was conducted with an empirical juridical approach, The conclusion of this research, basically regarding the period of settlement of a simple lawsuit in the Tebo Class II District Court for 25 days, or from 25 days depending on the litigant and the judge handling the case. The negligence of the judge in resolving the case will certainly get a reprimand from the head of the court regarding the non-implementation of the expectations of case settlement in a short time. Regarding how to determine whether a lawsuit is a simple case or an ordinary case in the Tebo District Court in accordance with the provisions of PERMA, but is constrained by the time-consuming registration process, and obstacles in the trial process because the parties are difficult to coordinate, and for the implementation of simple lawsuits it has been running quite effectively in the Tebo Class II District Court. Abstrak Mahkamah Agung Republik Indonesia telah menerbitkan suatu peraturan tentang gugatan sederhana berupa Peraturan Mahkamah Agung (PERMA) Nomor 2 Tahun 2015 tentang Tata Cara Penyelesaian Gugatan Sederhana yang kemudian diperbarui dengan PERMA Nomor 4 Tahun 2019 tentang Perubahan Atas PERMA Nomor 2 Tahun 2015 tentang Tata Cara Penyelesaian Gugatan Sederhana. Dengan ketetapan tersebut diharapkan penyelesaian gugatan perkara sederhana sesuai dengan asas peradilan Indonesia yang cepat, sederhana dan biaya ringan. Penelitian ini dilakukan untuk mengetahui bagaimana menentukan suatu gugatan yang diajukan merupakan gugatan perkara sederhana atau perkara biasa, dan melihat keefektivitasan pelaksanaan gugatan sederhana di Pengadilan Negeri Tebo Kelas II. Penelitian ini dilakukan dengan pendekatan yuridis empiris. Kesimpulan dari penelitian ini, pada dasarnya mengenai jangka waktu penyelesaian gugatan sederhana di Pengadilan Negeri Tebo Kelas II selama 25 hari, atau dari 25 hari tergantung pihak yang berperkara dan hakim yang menangani perkara tersebut. Kelalaian hakim dalam menyelesaikan perkara tentu mendapatkan teguran dari ketua pengadilan terkait tidak terlaksananya harapan penyelesaian perkara dengan waktu singkat. Terkait cara menentukan gugatan termasuk perkara sederhana atau perkara biasa di Pengadilan Negeri Tebo sesuai dengan ketentuan PERMA, namun terkendala proses pendaftaran yang memakan waktu, dan kendala di proses sidang karena pihak yang sulit dikoordinir, dan untuk pelaksanaan gugatan sederhana sudah berjalan cukup efektif di Pengadilan Negeri Tebo Kelas II. Â